Divergences on the environmental impact associated to the production of maritime pine wood in Europe: French and Portuguese case studies - González-García, Sara
Life Cycle Assessment (LCA) has become a common methodology to evaluate the environmental performance of forest systems in recent years. This study aims to estimate the environmental profile associated with maritime pine wood production in two representative European countries: Portugal and France. Different forest management regimes based on low and high intensive conditions were evaluated and differences in logging equipment, biomass yield and lifespan were also reported. The study was completed with a sensitivity analysis based on two allocation approaches (economic and volumetric) since biomass from thinning processes is harvested and can be used as a co-product.The production of maritime pine in Portugal under low intensity conditions should present the best environmental results with reductions of 50-94% in comparison with the worst scenario. It is mainly associated with the absence of forest activities in periods previous to the logging stage.French intensive forest scenario ranks as the second best alternative of pine wood production. The remaining scenarios reported worse results in terms of environmental impacts mostly due to the remarkable repetition of a selection of those forest activities with large fuel requirement (mainly on site preparation and stand establishment and tending).Regardless of the scenario, logging related activities such as final cutting and forwarding were identified as the hotspots mainly due to the fuel requirements. Fertilizer production (if required), thinning and cleaning processes reported also remarkable contributions to the categories under assessment.In addition, an economic estimation for each forest management scenario has been performed mainly considering fuel, machinery and labor costs. According to the results, the Portuguese low intensive scenario is the best choice together with the French intensive scenario under an economic point of view because of the lowest production costs per functional unit. Activities related with the logging stage have also been identified as economic hotspots.